Strengthening Children’s Religious And Moral Values In Shamil And Dodo Cartoon Film - Septianti, Fitria; Hafidz, Nur (Universitas Nahdlatul Ulama Surabaya, 2021)
The current era of education for children is experiencing a moral crisis in the aspects of religious and moral development. Religious and moral values ​​of children will be formed through interaction and environmental responses to an active five-sensory performance system. Cartoon films are a strategy for developing children's creativity. By presenting imaginative, interactive, and fun story events through the behavior and attitudes of the characters in cartoon films. The cartoon film Syamil and Dodo became a cartoon film by NCR Production which was made to educate children because it was rich in Islamic educational values ​​and religious and moral values ​​which were suitable to stimulate early childhood. The problem in this research is: